Supported Catalytically Active Supramolecular Hydrogels for Continuous Flow Chemistry. (6th November 2019) - Rodon Fores, Jennifer; Criado‐Gonzalez, Miryam; Chaumont, Alain; Carvalho, Alain; Blanck, Christian; Schmutz, Marc; Serra, Christophe A.; Boulmedais, F.; Schaaf, Pierre; Jierry, Loïc
Abstract: Inspired by biology, one current goal in supramolecular chemistry is to control the emergence of new functionalities arising from the self‐assembly of molecules. In particular, some peptides can self‐assemble and generate exceptionally catalytically active fibrous networks able to underpin hydrogels. Unfortunately, the mechanical fragility of these materials is incompatible with process developments, relaying this exciting field to academic curiosity. Here, we show that this drawback can be circumvented by enzyme‐assisted self‐assembly of peptides initiated at the walls of a supporting porous material. We applied this strategy to grow an esterase‐like catalytically active supramolecular hydrogel (CASH) in an open‐cell polymer foam, filling the whole interior space. Our supported CASH material is highly efficient towards inactivated esters and enables the kinetic resolution of racemates. This hybrid material is robust enough to be used in continuous flow reactors, and is reusable and stable over months. Abstract : CASH‐Flow : Katalytisch aktive supramolekulare Hydrogele (CASH), die auf porösen Polymerschäumen durch Enzym‐vermittelte Selbstorganisation synthetisiert wurden, sind ideale katalytisch aktive Phasen für Fluss‐Systeme. Ein Hydrogel, das aus einem bisphosphorylierten Heptapeptid hergestellt wurde, ermöglicht die effiziente Hydrolyse von Estern und kinetische Racematspaltungen.